Circadian clocks in antennal neurons are necessary and sufficient for olfaction rhythms in Drosophila. - Tanoue, S.; Krishnan, P.; Krishnan, B.; Dryer, S.E.; Hardin, P.E. (Current Biology, 2004)
The Drosophila circadian clock is controlled by interlocked transcriptional feedback loops that operate in many neuronal and nonneuronal tissues. These clocks are roughly divided into a central clock, which resides in the brain and is known to control rhythms in locomotor activity, and peripheral clocks, which comprise all other clock tissues and are thought to control other rhythmic outputs. We previously showed that peripheral oscillators are required to mediate rhythmic olfactory responses in the antenna, but the identity and relative autonomy of these peripheral oscillators has not been defined.Targeted ablation of lateral neurons by using apoptosis-promoting factors and targeted clock disruption in antennal neurons with newly developed dominant-negative versions of CLOCK and CYCLE show that antennal neurons, but not central clock cells, are necessary for olfactory rhythms. Targeted rescue of antennal neuron oscillators in cyc(01) flies through wild-type CYCLE shows that these neurons are also sufficient for olfaction rhythms.Antennal neurons are both necessary and sufficient for olfaction rhythms, which demonstrates for the first time that a peripheral tissue can function as an autonomous pacemaker in Drosophila. These results reveal fundamental differences in the function and organization of circadian oscillators in Drosophila and mammals and suggest that components of the olfactory signal transduction cascade could be targets of circadian regulation.